If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-8=4+4(x+5)
We move all terms to the left:
3x-8-(4+4(x+5))=0
We calculate terms in parentheses: -(4+4(x+5)), so:We get rid of parentheses
4+4(x+5)
determiningTheFunctionDomain 4(x+5)+4
We multiply parentheses
4x+20+4
We add all the numbers together, and all the variables
4x+24
Back to the equation:
-(4x+24)
3x-4x-24-8=0
We add all the numbers together, and all the variables
-1x-32=0
We move all terms containing x to the left, all other terms to the right
-x=32
x=32/-1
x=-32
| 4x-5=-x+5 | | (9x-4)=(3x=6) | | 14x(10)-7=21 | | 4/3x+3/5=6/15 | | -8=-1/13a | | 13-3b-2b=11 | | 2(5g-1=3 | | (x*x*x)=27/729 | | 5x/6=-30 | | 3x/4=-60 | | 16(x-3)=32 | | 19x.36=6.87 | | 1n-5=2 | | 1n+5=2 | | z-4.8=6.1 | | n/14=-14 | | -9x+7x=-24+24 | | -53.6=-6.7c | | (x+2)*(x-3)-(x+1)^2=0 | | 2(4y-4)-3=21 | | Y+4x=11.X=-1,0,4 | | x+2x+x+5=57 | | 11u+99=-77 | | 5.2=d/8 | | 23.4=-3.9s | | 2(x-5=20x) | | 2(x-5=20x | | 2(x-50=20x | | 6.4=f-5.2 | | 2x+-10=20x | | 6x-18=42-x | | 3(d-8)=2d+3 |